MARIA MADALENA E AS MULHERES NO CRISTIANISMO PRIMITIVO - Silva, Francisca Rosa da (2008)
The objective of this study is to research women s leadership in the primitive Christianity, starting from the figure of Mary Magdalene in Jo 20,1-18. The exegetic, view as well as research on women s situation in the first century, show: a) Women that followed Jesus were part of the disciples group, and Mary Magdalene had strong influence among them in the community; b) she accompanied Jesus since the beginning of his ministry in Galilee, and her leadership and authority in primitive Christianity conferred her the disciple status c) the Pericope that is studied has as a fundamental concept the conflict of leaderships among three traditions: John s, the Peter s and Mary Magdalene s. Comparing the Pericopes of John with certain Gnostic writings, its noticeable that in these writings Mary Magdalene s leadership is manifested with stronger intensity, and the conflict with Peter is more accentuated. She is considered the Master of the disciples. The research not only rescues the leader figure of Christianity, but also shows, via the exegesis, the process of the cooptation of women s leadership.(AU)